2021
DOI: 10.3390/ijms221910765
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic Acid Decreases Keloid Formation by Reducing Endoplasmic Reticulum Stress as Implicated in the Pathogenesis of Keloid

Abstract: Keloids are a common form of pathologic wound healing and are characterized by an excessive production of extracellular matrix. This study examined the major contributing mechanism of human keloid pathogenesis using transcriptomic analysis. We identified the upregulation of mitochondrial oxidative stress response, protein processing in the endoplasmic reticulum, and TGF-β signaling in human keloid tissue samples compared to controls, based on ingenuity pathway and Kyoto Encyclopedia of Genes and Genomes (KEGG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…this was consistent with our current results, and the inhibition of ER stress significantly decreased scar formation in a rabbit model [26].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…this was consistent with our current results, and the inhibition of ER stress significantly decreased scar formation in a rabbit model [26].…”
Section: Discussionsupporting
confidence: 94%
“…In another study, the inhibition of IRE1α also decreased scar formation and decreased XBP1 expression [25]. In a recent study, higher ER stress signaling was demonstrated in keloids than in normal tissues; this was consistent with our current results, and the inhibition of ER stress significantly decreased scar formation in a rabbit model [26]. These results suggested that XBP1, as a key regulator of UPR pathway, is closely related with keloid formation and may represent a potential therapeutic target for keloids.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Zhang et al 16 showed that TGF-β1 upregulated the expression of GRP78 and α-SMA in lung fibroblasts, while the ERS inhibitor taurodeoxycholic acid (TUDCA) attenuated the expression of these markers. In keloid tissue in rabbit, Kim et al 39 found that the relief of the ERS could effectively prevent scar formation. Boyko et al 34 reported that inhibition of IRE1 expression could prevent wound scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Genes with p -values < 0.05 and FC values ≥ 1.2 between the PM and non-PM groups were defined as DEGs. Functional characterization was performed using KEGG and IPA (Ingenuity Systems, Redwood City, CA, USA) to identify pathways with significant p -values and Z-scores [ 57 ]. The GEO submission number is GSE200463.…”
Section: Methodsmentioning
confidence: 99%